B-mode and Doppler ultrasonography in the assessment of the common carotid arteries of equines and mules and the relation with body mass, age and neck circumference - Fogaça, Jéssica L. [UNESP]; Castiglioni, Maria C.R. [UNESP]; Vettorato, Michel C. [UNESP]; Andrade, Danilo G.A. [UNESP]; Puoli-Filho, José N.P. [UNESP]; Fernandes, Marco A.R. [UNESP]; Machado, Vânia M.V. [UNESP] (FapUNIFESP (SciELO), 2019)
As age increases, changes in cardiovascular anatomy and physiology occur, even in the absence of disease. Thus, studies of vessel hemodynamics are considered primordial to detect any cardiovascular changes. The objective of this study has been to describe the parameters of B-mode and spectral Doppler ultrasonography in the evaluation of the common carotid arteries of 11 equine and 11 mules, and correlate with age, body mass and neck circumferences. The diameters, intima - media thickness (IMT), resistivity index (RI), pulsatility index (PI), systolic velocity (SV), diastolic velocity (DV), maximum velocity (MV), vascular flow index (VFI), body mass, age, circumference and neck length. Ultrasonographic variables were evaluated in three different region called cranial, middle and caudal. Equine females presented higher values regarding the body mass, age and neck length, as compared to the neck circumferences of the animals, those of the mules were superior. The age of the mules had a positive correlation with the body mass, diameter and neck circumferences, it has a negative correlation between age and vessel diameters. The body mass of the mules had a positive correlation with age and vessel diameters, and with vessel diameters and neck circumferences in equine females. The RI and PI variables had a positive correlation with body mass for mules, and with age for equine females. The DV had a negative correlation with body mass for both equine and mule females. Regarding the variables MV and VFI, age correlated negatively for mules, while it was not significant for equine females. It found a difference between equine females and mules in the correlations performed, with body mass, age, neck circumferences and between B-mode and Doppler ultrasonography variables.
Keywords: Age; Body mass; Carotid arteries; Doppler; Equines; Horses; INDEX TERMS: B-mode; Mules; Neck circumference; Ultrasonography